Telaah Pemikiran Al Kindi: Konsep Ketuhanan dalam Prespektif Islam - Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti; Fauzi, Sriyono (Lembaga Yasin AlSys, 2024)
Al-Kindi lived at a time when philosophy was not yet well known in the tradition of Islamic thought, precisely during the transition from traditional theology to philosophy. Al-Kindi was the first Arab to introduce philosophy into Arab thought and was given the title